Characteristics of Malaysian and Sulawesian Cocoa Beans and the Optimisation of Quality Through Blending - Leow, Min Min (1999)
Commercial Malaysian and Sulawesian cocoa were found to be significantly different (p<0.05) in the aspect of bean quality, fermentation index, fat content, polyphenol, alkaloids, volatile and non volatile acids. In other aspects such as melting point (cocoa butter), triglyceride, fatty acids and solid fat content (SFq the difference was found to be insignificant (p>0.05). More purple bean was found in the Sulawesian beans (78%) compared to the Malaysian beans (4%). The high content of polyphenol (epicatecbin = 34.72 mg/g) and alkaloids (theobromine = 30.40 mg/g, caffeine=0.678 mg/g) in Sulawesian beans showed a sign of under fermentation. Fermentation index further verify Sulawesian· beans (0.622) as under- fermented compared to the Malaysian beans (1.524). Cocoa beans with different fermentation level exhibited significant difference in cut test, melting temperature (Malaysian beans only), volatile and non-volatile acid, polyphenol, alkaloids, solid fat content and taste. Melting temperature of the Malaysian cocoa butter increase with fermentation. Non-volatile acids such as lactic, succinic and citric increased but malic and oxalic acids decreased with fermentation. All the volatile acid but propionic acid increased with fermentation. On the other hand, polyphenol and alkaloids decreased drastically as fermentation proceeds. In the aspect of taste, all less fermented cocoa beans from Malaysia and Sulawesi were more bitter and astringent but the more fermented cocoa beans produces cocoa liquor with a more sour taste. The qualities that the blended cocoa beans needs to express are a better cocoa/ chocolaty taste, less bitter, less astringent, less sour and preferably with the presence of nutty flavour. Cocoa blends found to have the most favourable taste are blends of 4 days fermented Malaysian cocoa beans and 2 days fermented Sulawesian beans at the ratio of 75:25 (I2M4/25) and blends of 6 days fermented Malaysian cocoa beans and 2 days fermented Sulawesian beans at the ratio of 25:75 (I2M6/75).